The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1186/s12931-022-01998-8
|View full text |Cite
|
Sign up to set email alerts
|

Air pollution and hospitalization of patients with idiopathic pulmonary fibrosis in Beijing: a time-series study

Abstract: Background A small number of studies suggested that air pollution was associated with idiopathic pulmonary fibrosis (IPF) exacerbation, incidence and mortality. However, no studies to date were conducted in regions where air pollution is substantial. We aimed to investigate whether there are associations between acute increases in air pollution and hospitalization of patients with a confirmed primary diagnosis of IPF in Beijing. Methods Daily count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 40 publications
(69 reference statements)
0
16
0
Order By: Relevance
“…Three studies were conducted each in Spain ( 53 , 54 , 63 ) and South Korea ( 43 , 57 , 64 ). Two studies each came from France ( 47 , 65 ) and mainland China ( 59 , 60 ). The remaining studies were conducted in Italy ( 45 ), Chile ( 51 ), Taiwan ( 52 ), Japan ( 55 ), Greece ( 56 ), the United Kingdom ( 61 ), and Australia ( 66 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three studies were conducted each in Spain ( 53 , 54 , 63 ) and South Korea ( 43 , 57 , 64 ). Two studies each came from France ( 47 , 65 ) and mainland China ( 59 , 60 ). The remaining studies were conducted in Italy ( 45 ), Chile ( 51 ), Taiwan ( 52 ), Japan ( 55 ), Greece ( 56 ), the United Kingdom ( 61 ), and Australia ( 66 ).…”
Section: Resultsmentioning
confidence: 99%
“…Among the 24 studies incorporated in the analysis, seven studies scrutinized the link between short-term exposure to air pollution and its impact on health outcomes ( 43 , 46 , 49 , 51 , 55 , 59 , 60 ). Fourteen studies delved into the connection between long-term exposure to air pollution and health outcomes ( 44 , 45 , 48 , 50 , 52 , 54 , 56–58 , 62 , 64–66 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, pollutants like O 3 and SO 2 , surpassing predefined thresholds on a limited number of days (0.52% for O 3 and 0.37% for SO 2 ), were included for a more accurate evaluation of atmospheric pollutants’ influence on hospitalization rates for acute coronary events. Subsequently, we conducted an analysis for each increment of ≥10 μg/m 3 in environmental pollutants at various time lags (e.g., lags 03, 05, and 07) concerning NSTE-ACS incidents [ 28 , 29 ]. Including a time lag is essential, as it allows for the observation of the impact of pollutant exposure not only on the day of exposure but also over subsequent days.…”
Section: Methodsmentioning
confidence: 99%
“…It has a poor prognosis, with a median survival of 3–5 years without treatment 1–3. Several studies have demonstrated the harmful effects of air pollution on IPF prognosis, including incidence,4 5 acute exacerbation (AE),6 7 hospitalisation,8 9 changes in lung function10–12 and mortality 13 14. Particulate matter (PM) refers to the mixture of solid particles and liquid droplets found in the air.…”
Section: Background and Rationalementioning
confidence: 99%